Maize bHLH55 functions positively in salt tolerance through modulation of AsA biosynthesis by directly regulating GDP-mannose pathway genes. (January 2021) - Yu, Chunmei; Yan, Ming; Dong, Huizhen; Luo, Jie; Ke, Yongchao; Guo, Anfang; Chen, Yanhong; Zhang, Jian; Huang, Xiaosan
Highlights: Ascorbic acid (AsA) is an important antioxidant and co-factor in many plants. In the ZmbHLH55 knock-down mutant ( zmbhlh55 ), the AsA content was decreased. ZmbHLH55 was bound to the E boxes of the GDP-mannose pathway genes. We have uncovered one of the regulation mechanisms for AsA biosynthesis in maize. Abstract: Ascorbic acid (AsA) is an antioxidant and enzyme co-factor that is vital to plant development and abiotic stress tolerance. However, the regulation mechanisms of AsA biosynthesis in plants remain poorly understood. Here, we report a basic helix-loop-helix 55 ( ZmbHLH55 ) transcription factor that regulates AsA biosynthesis in maize. Analysis of publicly available transcriptomic data revealed that ZmbHLH55 is co-expressed with several genes of the GDP-mannose pathway. Experimental data showed that ZmbHLH55 forms homodimers localized to the cell nuclei, and it exhibits DNA binding and transactivation activity in yeast. Under salt stress conditions, knock down mutant ( zmbhlh55 ) in maize accumulated lower levels of AsA compared with wild type, accompanied by lower antioxidant enzymes activity, shorter root length, and higher malondialdehyde (MDA) level. Gene expression data from the WT and zmbhlh55 mutant, showed that ZmbHLH55 positively regulates the expression of Z mPGI2, ZmGME1, and ZmGLDH, but negatively regulates ZmGMP1 and ZmGGP . Furthermore, ZmbHLH55 -overexpressing Arabidopsis, under salt conditions, showed higher AsA levels, increased rates of germination, and elevated antioxidant enzyme activities. In conclusion, these results have identified previously unknown regulation mechanisms for AsA biosynthesis, indicating that ZmbHLH55 may be a potential candidate to enhance plant salt stress tolerance in the future.